Energy-Efficiency of Conveyor Belts in Raw Materials Industry - Marasová, Daniela; Hardygora, Monika; Bajda, Mirosław (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on research related to the energy efficiency of conveyor transportation. The solutions presented in the Special Issue have an impact on optimizing, and thus reducing, the costs of energy consumption by belt conveyors. This is due, inter alia, to the use of better materials for conveyor belts, which reduce its rolling resistance and noise, and improve its ability to adsorb the impact energy from the material falling on the belt. The use of mobile robots designed to detect defects in the conveyor's components makes the conveyor operation safer, and means that the conveyor works for longer and there are no unplanned stops due to damage.